An unusual case of acute respiratory failure in a patient with pulmonary veins stenosis late after catheter ablation of atrial fibrillation: a case report and the review of the literature. Issue 1 (December 2015) - Spadaro, Savino; Saturni, Sara; Cadorin, Delia; Colamussi, Maria; Bertini, Matteo; Galeotti, Roberto; Cappato, Riccardo; Ravenna, Franco; Volta, Carlo
Abstract Background Atrial fibrillation (AF) can be treated with percutaneous catheter ablation procedures into the left atrium. Pulmonary veins stenosis (PV) stenosis is a severe complication of this procedure. Case presentation we report a case of late hemoptysis secondary to severe PV stenosis in a man who underwent AF ablation 9 months before onset of symptoms. He presented four episodes of bleeding and developed an acute respiratory failure (ARF). Parameters of respiratory mechanics and medical investigation did not show any abnormalities. Only computed tomography (CT) angiography showed stenosis of 3 out of 4 native PVs. PV balloon dilatation in all affected PVs and a stent was implanted in 1 of the 3 PVs with full restoration of respiratory function during 1 year follow-up. Conclusion PV stenosis may be the underlying cause of recurrent haemoptysis after AF ablation in the presence of normal respiratory parameters. This diagnosis can be confirmed by means of CT angiography and magnetic resonance imaging can provide accurate localization of stenosis.